Abandoned - Brennan, Allison (New York : Minotaur Books, 2018)
"Investigative reporter Max Revere has cracked many cases, but the one investigation she's never attempted is the mystery from her own past. Her mother abandoned her when she was nine, sending her periodic postcards, but never returning to reclaim her daughter. Seven years after the postcards stop coming, Martha Revere is declared legally dead, with no sign of what may have happened to her. Until now. With a single clue--that her mother$1 (Bs car disappeared sixteen years ago in a small town on the Chesapeake Bay--Max drops everything to finally seek the truth."--s
Keywords: Women journalists -- Fiction; Mothers and daughters -- Fiction; Detective and mystery fiction